Analyzing Occupational Hazards of Top Turn Operator in Compost Factories by JHA Method (Case Study: Halgheh Darreh Landfill and Treatment Center in Karaj) - Fariba Jalali; Javid Mohemsaz; Sepehr Akhlaghifard; Nahid Ghobadi; Abbas Esmaeili (Journal of Advances in Environmental Health Research)
Background: There are biologically harmful factors in waste management and, if neglected, they can bear detrimental consequences for the organization and its staff. Regarding the importance of the healthcare of the personnel working in waste management, this study has been conducted to identify and assess the sanitary and safety hazards threatening Top Turn operators working in urban compost waste factories.Methods: In this sectional-descriptive study which was conducted in Karaj’s Waste Management Methods: Organization Compost Factory in the year 2021, job hazard analysis (JHA) method was used in order to calculate the sanitary and safety risk caused by deleterious factors. First, the job in mind was selected and its responsibilities as well as the degree and probability of each risk factor were specified; then the risks were assessed according to risk assessment matrix based on MIL-STD-882B standard.Results: A total of 8 risk factors were identified for the top turn operator, and respectively 2 factors were ranked as unacceptable, 4 factors as undesirable, 2 factor as acceptable but needing review. Using the JHA method the sanitary and safety hazards can be assessed and ranked proportionate to the risk level.Conclusion: Regarding the importance of sanitary hazards, in addition to identifying and assessing them, it is suggested that controlling measures be carried out in order to reduce and repress risk levels so that the related occupational accidents and diseases and, as a result their heavy expenses can be prevented.